Muslim Educational System in the Sub-Continent (Al-Qamar, 2022)
When any nation conquers any country, the conquered nation gives up its national characteristics and traditions and follows the footsteps of conqueror. But sensible and perceptive Muslims of India released the danger of ruler of that time and advised the Muslims of Sub-Continent to get education to overcome the danger. The Muslim’s thinking was based on foresightedness because after being deprived of political power there remained nothing except education. It was education through which they could protect their identity. The scholars of sub-continent focused their full attention to the teachings of traditional syllabus. For this purpose, Arabic Madaris/Institutes were established, through these Madaris. The Muslims paid attention for the development of Arabic language with Tafseer, Hadees, and Fiqh. The Muslims did not lose their own educational system instead of being enslaved. In Sub-Continent regular system of Madaris was established with the arrival of the Muslims in the sub-continent.
Keywords: Muslim Educational System; Characteristics; Sub-Continent